Steelband Jamboree - Unknown (Sunday Guardian)
The U.S. Naval Station at Chaguaramas and the Trinidad and Tobago Steel Orchestras Association have completed plans for the steel band jamboree at the Naval Base. The Tenth Naval District Steelband from Puerto Rico, Invaders from Port-of-Spain and Sundowners from San Fernando will be taking part. In addition, the Mighty Dougla, the 1961 Calypso King will perform.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- United States; Steel band music -- Trinidad and Tobago